Rates, flux densities, and spectral indices of meteor radio afterglows. Issue 7 (9th July 2016) - Obenberger, K. S.; Dowell, J. D.; Hancock, P. J.; Holmes, J. M.; Pedersen, T. R.; Schinzel, F. K.; Taylor, G. B.
Abstract: Using the narrowband all‐sky imager mode of the Long Wavelength Array (LWA1), we have now detected 30 transients at 25.6 MHz, 1 at 34 MHz, and 93 at 38.0 MHz. While we have only optically confirmed that 37 of these events are radio afterglows from meteors, evidence suggests that most, if not all, are. Using the beam‐forming mode of the LWA1, we have also captured the broadband spectra between 22.0 and 55.0 MHz of four events. We compare the smooth, spectral components of these four events and fit the frequency‐dependent flux density to a power law, and find that the spectral index is time variable, with the spectrum steepening over time for each meteor afterglow. Using these spectral indices along with the narrowband flux density measurements of the 123 events at 25.6 and 38 MHz, we predict the expected flux densities and rates for meteor afterglows potentially observable by other low‐frequency radio telescopes. Key Points: We have computed rates of meteor radio afterglows We have measured the spectra of four meteor radio afterglows and have fit them to a power law We use the power law fit and the measured rates to predict event rates for other telescopes at other frequencies